The Application of Process Approach in Enhancing Paragraph Writing Skills of SMA Negeri 1 Lembang - Situngkir, Debby Anelia (LPPM Universitas Advent Indonesia, 2019)
Enhancing paragraph writing skill of students addresses the issues of writing. To see the paragraph writing skill enhancement of students and finding out the significant difference in paragraph writing skill enhancement between students acquired Individual Process Approach and students acquired Collaborative Process Approach are the aims of this research. To get the aims of this research used quantitative research. Also, researcher conducted paragraph writing pre-test and post-test, as an instrument, to 64 second year students of SMA Negeri 1 Lembang. Then researcher analyzed students’ pre-test and post-test achievement by using Statistical Package for the Social Science (SPSS). The results are paragraph writing skills of students enhanced and there is significant difference in paragraph writing skill enhancement between students acquired Individual Process Approach and students acquired Collaborative Process Approach. It implies that Process Approach enhance paragraph writing skill of students.